1965
DOI: 10.1007/bf01253806
|View full text |Cite
|
Sign up to set email alerts
|

Measles associated chromosome breakage

Abstract: In 1962 we reported chromosome breaks in peripheral white blood cells (1) of patients with clinical measles (rubeola). This work was part of a study on the relationship between viruses, chromosomes, and carcinogenesis. The first system studied in this project was a tumor virus, the Schmidt-Ruppin strain of the Rous sarcoma virus. This produces tumors not only in the chicken and fowl but also in a wide variety of mammals (2). When this virus was studied in the rat it was noted that chromosome breakage occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Based on the morphologic characterization, chromosome fragmentation might offer insight into the mechanism of the long-described phenomenon of chromosome pulverization (36). Frequently observed after viral infection and thought to occur from cell fusion, chromosome pulverization has often been linked to the prematurely condensed chromosomes and thus was thought of as occurring in interphase nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the morphologic characterization, chromosome fragmentation might offer insight into the mechanism of the long-described phenomenon of chromosome pulverization (36). Frequently observed after viral infection and thought to occur from cell fusion, chromosome pulverization has often been linked to the prematurely condensed chromosomes and thus was thought of as occurring in interphase nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Leukopenia and lymphopenia are com mon during active measles infection [14,15], and the virus has been cul tured from blood leukocytes during that time [16]. The studies of Ni chols et al [17,18] have shown that addition of measles virus to a varie ty of tissue cells, including human leukocytes, leads to several types of chromosomal abnormalities, particularly in proliferating cells [19], N orrby et al [20] have shown that measles virus treated in a variety of ways to render it noninfective retains several biologic characteristics, including the capacity to induce some cytopathogenic effects. Although studies uti lizing autoclaved virus were not reported by this group, preliminary in vestigations in our laboratory suggest that autoclaved preparations may retain some of the biological activities of the measles virus, although non infective.…”
Section: Discussionmentioning
confidence: 99%
“…MCDs also occur in response to various types of stress, often when cell cycle checkpoint function is abrogated, though they can also occur in normal tissue . C-Frag, for instance, has been shown to occur in swine lymphocytes in response to vaccination [Nichols and Levan, 1965]. It also occurs in response to chemotherapeutic treatments, gene defects, ER stress, HSP90 inhibition, genomic instability and centrosome amplification.…”
Section: Heterogeneity Of Factors That Induce Deathmentioning
confidence: 99%